Sao Joaquim Plateau, Parana Magmatic Province: Field Features and Issues - Besser, Marcell Leonard; Gouvea Vasconcellos, Eleonora Maria; Ranalli Nardy, Antonio Jose [UNESP] (Univ Fed Parana, Editora, 2015)
The Sao Joaquim Plateau (SJP) is located in the Southern Highlands of Santa Catarina, which lays on the extreme southeast of the Brazilian Southern Highlands. The plateau is above Serra Geral Flood Basalts, which are organized mainly as pahoehoe flows, but also as a'a 'flows. The felsic rocks of SJP configure large tabular flows which thickness rises to 100 m and are widespread over 280 km(2). Isolated hills in the plateau surroundings conserve remaining portions of these lava flows, evidence that their extension were much larger and is now reduced by erosion. The stratigraphy overlying basalt sequence is commonly architected as follows: (1) decametric level rocks of transitional character, represented by gray - reddish or red volcanites, massive to amygdaloidal, which may contain decimetric geodes; (2) metric wavy level of amigdaloidal yellowish saprolite with stretched amygdales currently filled by white clays, autoclastic breccias formed by weathered pumice/scoria and pitchstone lenses; (3) basal decametric felsic level formed by pitchstone lenses and aphanitic rocks with banded laminar plane - parallel flow, twisted or folded flow; (4) decametric felsic level with platy joints; (5) thickness (< 65 m) felsic level formed by thin phaneritic massive rocks, with or without tabular joints; (6) in the upper massive level appear rare amygdales. Due to lack of evidence to assign an ignimbritic genesis to these rocks, such volcanites of Sao Joaquim plateau are preliminarily designated as Plateau Rhyolites of the Serra Geral Formation.
Keywords: Parana Province; Sao Joaquim Plateau; lava stratigraphy; plateau rhyolites